2013
DOI: 10.1177/1082013212442194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high hydrostatic pressure on overall quality parameters of watermelon juice

Abstract: High hydrostatic pressure as a kind of non-thermal processing might maintain the quality of thermo-sensitive watermelon juice. So, the effect of high hydrostatic pressure treatment on enzymes and quality of watermelon juice was investigated. After high hydrostatic pressure treatment, the activities of polyphenol oxidase, peroxidase, and pectin methylesterase of juice decreased significantly with the pressure (P < 0.05). Inactivation of polyphenol oxidase and peroxidase could be fitted by two-fraction model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 61 publications
(103 reference statements)
2
19
0
Order By: Relevance
“…Two different empirical models were developed to describe the PME and PG inactivation in tomato juice having pH 4.2 (Crelier and others ). However, the first‐order inactivation model was found to be suitable for PG in tomato juice (pH 4.4) as reported by Fachin and others () and for PME in watermelon juice (Liu and others ). Buckow and others () fitted the n th‐order kinetic model for the inactivation of PPO in cloudy apple juice (Figure ).…”
Section: Modeling Of High‐pressure Inactivation Of Fruit Enzymessupporting
confidence: 64%
“…Two different empirical models were developed to describe the PME and PG inactivation in tomato juice having pH 4.2 (Crelier and others ). However, the first‐order inactivation model was found to be suitable for PG in tomato juice (pH 4.4) as reported by Fachin and others () and for PME in watermelon juice (Liu and others ). Buckow and others () fitted the n th‐order kinetic model for the inactivation of PPO in cloudy apple juice (Figure ).…”
Section: Modeling Of High‐pressure Inactivation Of Fruit Enzymessupporting
confidence: 64%
“…predicted that PPO and POD in pineapple puree followed first-order decay (n = 1) within 200-500 MPa/30-60°C. Consequently, PPO and POD from other fruits were also inactivated exponentially (or apparent first-order) with time within high pressure domain like PPO in peach juice ; PPO and POD in watermelon juice (Liu, Zhao, Zou, & Hu, 2013); PPO in avocado and so on. However, Buckow et al (2009) reported that inactivation of apple PPO followed nth order model with n = 2.2.…”
Section: Model Fitting To Nth Order Kineticsmentioning
confidence: 99%
“…Similar type of empirical model considering both Arrhenius and Eyring's equations has been developed in several kinetic studies (Boulekou et al, 2010;Liu et al, 2013;Polydera et al, 2004). The single multi-parameter equation (Eq.…”
Section: Inactivation Rate Constant As a Function Of Pressure And Temmentioning
confidence: 99%
“…(3): [31] (%) inactivation = 100 − Enzyme activity after treatment Enzyme activity before treatment × 100 (3)…”
Section: Pme Activitymentioning
confidence: 99%